Enhance The Creativity Of Fiqh Teachers In Order To Improve Students’ Learning Motivation At Mts Dinul Hasanah Rokan Hilir - Imran Rido; Siti Halimah; Laela Hamidah; Siti Aisyah (CV. AFDIFAL MAJU BERKAH, 2025)
This community service program aims to enhance the creativity of Fiqh teachers in order to improve students’ learning motivation at MTs Dinul Hasanah Rokan Hilir. The program was designed using a participatory and collaborative approach, involving teachers actively in all stages of the activities. The implementation process began with problem identification through classroom observations and needs analysis, followed by the preparation of training materials focused on creative and innovative teaching strategies. The training was conducted through socialization sessions, interactive workshops, and simulations that allowed teachers to practice student-centered, contextual, and technology-integrated learning methods. Evaluation was carried out using pre- and post-tests, reflective interviews, and continuous mentoring to assess teachers’ pedagogical improvement and the application of newly acquired techniques in classroom practice. The results indicate a significant improvement in teachers’ instructional creativity, confidence, and ability to design engaging learning activities. Furthermore, students showed increased motivation, participation, and enthusiasm during Fiqh lessons after the implementation of creative teaching strategies. Overall, the program demonstrates that creativity-enhancement training combined with mentoring is an effective strategy to improve the quality and meaningfulness of Fiqh learning in madrasah settings.